Making a virtue out of necessity: The effect of negative interest rates on bank cost efficiency - Giuseppe Avignone; Claudia Girardone; Cosimo Pancaro; Livia Pancotto; Alessio Reghezza (European Central Bank (ECB), 2022)
Do negative interest rates affect banks' cost efficiency? We exploit the unprecedented introduction of negative policy interest rates in the euro area to investigate whether banks make a virtue out of necessity in reacting to negative interest rates by adjusting their cost efficiency. We find that banks most affected by negative interest rates responded by enhancing their cost efficiency. We also show that improvements in cost efficiency are more pronounced for banks that are larger, less profitable, with lower asset quality and that operate in more competitive banking sectors. In addition, we document that enhancements in cost efficiency are statistically significant only when breaching the zero lower bound (ZLB), indicating that the pass-through of interest rates to cost efficiency is not effective when policy rates are positive. These findings hold important policy implications as they provide evidence on a beneficial second-order effect of negative interest rates on bank efficiency.
Keywords: E43; E44; E52; G21; F34; 330; NIRP; Difference-in-differences; Stochastic frontier approach; Bank cost efficiency